Ringworm in calves: risk factors, improved molecular diagnosis, and therapeutic efficacy of an Aloe vera gel extract - Yasmine H. Tartor (BMC Veterinary Research, 2020)
Abstract Background Dermatophytosis in calves is a major public and veterinary health concern worldwide because of its zoonotic potential and associated economic losses in cattle farms. However, this condition has lacked adequate attention; thus, to develop effective control measures, we determined ringworm prevalence, risk factors, and the direct-sample nested PCR diagnostic indices compared with the conventional methods of dermatophytes identification. Moreover, the phenolic composition of an Aloe vera gel extract (AGE) and its in vitro and in vivo antidermatophytic activity were evaluated and compared with those of antifungal drugs. Results Of the 760 calves examined, 55.79% (424/760) showed ringworm lesions; 84.91% (360/424) were positive for fungal elements in direct-microscopy, and 79.72% (338/424) were positive in culture. Trichophyton verrucosum was the most frequently identified dermatophyte (90.24%). The risk of dermatophytosis was higher in 4–6-month-old vs. 1-month-old calves (60% vs. 41%), and in summer and winter compared with spring and autumn seasons (66 and 54% vs. 48%). Poor hygienic conditions, intensive breeding systems, animal raising for meat production, parasitic infestation, crossbreeding, and newly purchased animals were statistically significant risk factors for dermatophytosis. One-step PCR targeting the conserved regions of the 18S and 28S genes achieved unequivocal identification of T. verrucosum and T. mentagrophytes in hair samples. Nested-PCR exhibited an excellent performance in all tested diagnostic indices and increased the species-specific detection of dermatophytes by 20% compared with culture. Terbinafine and miconazole were the most active antifungal agents for dermatophytes. Gallic acid, caffeic acid, chlorogenic acid, cinnamic acid, aloe-Emodin, quercetin, and rutin were the major phenolic compounds of AGE, as assessed using high-performance liquid chromatography (HPLC). These compounds increased and synergized the antidermatophytic activity of AGE. The treated groups showed significantly lower clinical scores vs. the control group (P < 0.05). The calves were successfully treated with topical AGE (500 ppm), resulting in clinical and mycological cure within 14–28 days of the experiment; however, the recovery was achieved earlier in the topical miconazole 2% and AGE plus oral terbinafine groups. Conclusions The nested PCR assay provided a rapid diagnostic tool for dermatophytosis and complemented the conventional methods for initiating targeted treatments for ringworm in calves. The recognized antidermatophytic potential of AGE is an advantageous addition to the therapeutic outcomes of commercial drugs.